EDUCATORS’ WORLDVIEW ETHICS AND THE CHANGE OF TECHNOLOGICAL PARADIGMS (BASED ON RUSSIAN AND MONGOLIAN EXPERIENCE) - Nikolaeva, Alla Dmitrievna; Alekseeva, Irina Stepanovna; Kolpakova, Avgustina Petrovna; Nakhodkin, Vasiliy Vasilievich; Gotovtseva, Niurgustana Gennadievna (International Journal of Psychosocial Rehabilitation, 2020)
This article highlights the process of a future teacher’s worldview and ethics formation while nurturing the human capital of an innovative economy and environment containing new technological paradigms. The system for teacher education is founded on moral and ethical values, and changes in technological paradigms on these bases leads to the formation of new value systems. In the context of these changes, the prospects for the development of a future teacher’s worldview and ethics development have been identified. The authors identify two factors that influence the formation of pedagogical ethics: (i) the natural and climatic environment and factors associated with the implementation of ethno-pedagogical principles of education; and (ii) the scientific and technological revolution and related processes of intensive economic innovation development. In a changing technological environment, the worldview of a modern teacher is influenced by their attitude toward nature, society, and different aspects of the surrounding reality, as well as themselves and their own life, which is expressed through beliefs, views, ideals, and value orientations that determine the spiritual and moral spheres of their personality, worldview orientation, consciousness, and thinking. The sociocultural environment and open sociocultural educational space become factors that determine the regional features of historical and modern educational practices. These factors also significantly impact pedagogical processes and the formation of ethics, innovative worldviews, consciousness, and thinking patterns of both the teacher and the people in the educational institution (under his/her professional influence) and, at the appropriate level, in society. The importance of the influence of environmental consciousness and sociocultural factors on the formation of students’ new ethical foundations, which are related to the understanding of existing environmental and social problems, is confirmed by the empirical data provided.